2019
DOI: 10.21053/ceo.2019.00304
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Novel Hereditary Hemorrhagic Telangiectasia Variants in an Austrian Patient Cohort

Abstract: Objectives Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal dominant genetic disorder characterized by pathogenic blood vessel development and maintenance. HHT type 1 (HHT1) and type 2 (HHT2) are caused by variants in endoglin (ENG) and activin receptor-like kinase-1 (ACVRL1), respectively. The aim of this study was to identify the spectrum of pathogenic variants in ENG and ACVRL1 in Austrian HHT families.Methods In this prospective study, eight Austrian HHT families were screened for variants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In the ACVRL1 mutation, one unpublished and three known variants were identified. The gene mutation study revealed nonsense, frameshift, splice donor, and missense variants [6]. These patterns are similar to those reported in previous studies from other countries.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In the ACVRL1 mutation, one unpublished and three known variants were identified. The gene mutation study revealed nonsense, frameshift, splice donor, and missense variants [6]. These patterns are similar to those reported in previous studies from other countries.…”
supporting
confidence: 78%
“…Koenighofer et al [6] identified three unpublished, five known, and one silent variant in ENG and ACVRL1 from eight unrelated, nonconsanguineous families in Austria. Two novel variants and one known variant were identified in the ENG mutation.…”
mentioning
confidence: 99%
“…R195 includes mutations in five genes: FGFR2 (endometrial carcinoma [Dutt et al, 2008 ], breast neoplasm [Chang et al, 2016 ]), FLT3 (leukemia [Zhang et al, 2014 ]), KIT (gastrointestinal stromal tumors [Fornasarig et al, 2020 ]), MAP2K1 (melanoma [Emery et al, 2009 ]), and PDGFRA (gastrointestinal stromal tumors [Corless et al, 2005 ]). R195 also includes 13 non‐cancer‐related mutations in five genes (Figure 2 ): FGFR3 (hypochondroplasia [Xue et al, 2014 ]), PDGFRB (myofibromatosis [Arts et al, 2016 ]), MAP2K1 and MAP2K2 (cardio‐facio‐cutaneous syndrome [Schulz et al, 2008 ]), and ACVRL1 (telangiectasia [Koenighofer et al, 2019 ]). D274 locates in activation loop of kinase domain and includes mutations from two genes: BRAF (melanoma [Maldonado et al, 2003 ]) and STK11 (lung cancer [Ji et al, 2007 ]).…”
Section: Resultsmentioning
confidence: 99%
“…A study on Danish patients with HHT showed that ENG pathogenic variants were found in 47 families (44%), AVCRL1 pathogenic variants in 45 families (42%), SMAD4 pathogenic variants in three families (3%), and unknown mutations in 12 families (11%) among 107 unrelated families [ 18 ]. In an Austrian patient cohort, pathogenic variants in ENG (37.5%) and ACVRL1 (62.5%) were identified as the cause of HHT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%